Conventionalized politeness in Singapore Colloquial English - Stadler, Stephanie (2020)
Politeness is a phenomenon that has received a great deal of attention, especially with reference to varieties of English. Although societal norms vary somewhat across cultural contexts, most varieties of English seem to show a preference for polite and face-conscious routines and for indirect and somewhat circumlocutionary forms of speech. Singapore Colloquial English (SCE) has received rather little attention in terms of politeness research. This paper explores politeness in the Singaporean cultural context and found that, while conventionalized indirectness is practiced in Singapore Standard English, SCE shows a strong preference for a conventionalized lack of explicit politeness and for systematic conversational brevity.